Efektivitas Perencanaan Anggaran Pada Dinas Kesehatan Provinsi Sulawesi Utara - Melope, Frets; Tampi, Johny R. E.; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
This study aims to gain knowledge and understanding of the scientific basis through an analysis of the effectiveness of budget planning in North Sulawesi Provincial Health Office are useful for the development of knowledge management development resources. With the method used in this study is qualitative.Based on the results and discussion, this study concludes that the achievement of the effectiveness of budget planning has not fully pay attention to aspects of quantity, quality and impact of services. Effective budget planning yet seen the success of the program has not Adequacy Ratio Power Dentist, Infants aged 0-6 months exclusively breastfed, proportion of population aged 15-24 years (married/unmarried) who have comprehensive knowledge about HIV-AIDS and the number of districts/municipalities implementing HMIS technology.Keywords: Effectiveness, Budget Planning, Health Services.